NEW «PARASITIC CLASS»: ON THE CONCEPT OF MIKHAIL VOSLENSKY - Сергій САВЧЕНКО; Катерина ПРОКОФ’ЄВА; Оксана РЕШЕТІЛОВА (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The article explores the phenomenon of the nomenklatura as a unique socio-political institution in the context of democratic transformations within post-Soviet societies. An analysis of Mikhail Voslensky’s works reveals the mechanisms of nomenklatura functioning and aids in understanding the structural challenges of overcoming the totalitarian legacy. The core of the article focuses on a comparative analysis of Voslensky’s concept. Born in Ukraine, Voslensky had a successful career within the Soviet system before emigrating to West Germany in 1972. His seminal work, «Nomenklatura» (1980), presents a critical analysis of the revolutionary movement’s transformation into a new ruling class. Voslensky identifies the nomenklatura as a distinct class that uses a system of privileges to maintain its dominance and exert social control. He meticulously documents the institutional mechanisms of nomenklatura domination, uncovering the interplay between party hierarchy and material privileges. Particular attention is paid to the subordination of the security forces to party control through mechanisms of the Central Committee, which minimized risks to the nomenklatura system. The article includes a comparative analysis of Voslensky’s and Milovan Djilas’s approaches to the «new class» of socialist societies. Unlike Djilas, who believed in the potential of «true» communism, Voslensky fully breaks away from the system. He refutes the thesis about the nomenklatura’s modernizing role, pointing instead to the robust developmental dynamics of pre-revolutionary Russia. The study identifies limitations and shortcomings in Voslensky’s concept. Despite his profound analysis of the Soviet nomenklatura, Voslensky failed to recognize similar mechanisms of social stratification within Western democracies. His excessive idealization of the West hindered the application of his theory to a broader context of elite formation in various state systems. Additionally, Voslensky’s research, rooted primarily in personal experience, does not adequately explore the historical and cultural nature of the nomenklatura, its genesis, or potential analogs in other systems. Nonetheless, his theoretical contributions provide a valuable foundation for developing new models of democratic governance.